Chemical Characterization and Source Apportionment of Atmospheric Particles Across Multiple Sampling Locations in Faisalabad, Pakistan. Issue 7 (8th April 2016) - Javed, Wasim; Wexler, Anthony S.; Murtaza, Ghulam; Iqbal, Muhammad Mazhar; Zhao, Yongjing; Naz, Tayyaba
Abstract : Atmospheric particles (total suspended particles, TSPs) mass samples (288) were collected by high volume samplers at nine sampling locations in Faisalabad, Pakistan from May 2012 to April 2013. These TSP mass samples were subjected to gravimetric and quantitative chemical analyses for determining trace elements (Pb, Cd, Ni, Zn, Cu, Fe) using atomic absorption spectroscopy and water‐soluble cations (Ca 2+, Mg 2+, Na + and K +, NH4 + ) and anions (Cl −, SO4 2−, and NO3 − ) by ion chromatography. The average TSP mass and elemental concentrations at all locations were found to be highest during the dry and lowest during the wet season. The crustal elements Ca, Fe, Mg, and Na were the largest contributors to TSP mass while elements of anthropogenic origin Pb, Cd, Ni, Cu, and Zn had relatively lower concentrations and also showing a high spatial variation. The concentration of TSP and elements exhibited the maxima at the sampling locations characterized by intensive industrial and vehicular activities. The wind rose analysis and the UNMIX model applied to chemical speciation data both identified the same three primary sources of TSP: power plant/refinery, brick kilns, and roadways. The normalized dot product was successfully used to quantify the similarity between different source profiles extracted from UNMIX model. The coupling of UNMIX with wind direction analysis complemented each other and provided a complete assessment of source contributions and locations. Abstract : Airborne particles mass and element concentrations are determined at nine sampling locations in Faisalabad, Pakistan, during 2012–2013. The particles and elements concentrations are found the highest at the industrial and traffic locations and during the dry season. Three main pollution sources, power plant/refinery, brick kilns, and roadways, are identified in the local area using the combination of wind direction analysis and UNMIX model.